2022
DOI: 10.1186/s13287-022-02923-y
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stromal cells increase the formation of collagens through paracrine and juxtacrine mechanisms in a fibroblast co-culture model utilizing macromolecular crowding

Abstract: Background Adipose-derived stromal cells (ASCs) possess a multitude of regenerative capabilities, which include immunomodulation, angiogenesis, and stimulation of extracellular matrix (ECM) remodeling. However, the underlying mechanisms leading to ECM remodeling remain largely elusive and highlight the need for functional in vitro models for mode of action studies. Therefore, the purpose of this study was to develop an in vitro co-culture model to investigate the capabilities of ASCs to modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In another study, ASC-CM reduced the synthesis of collagen and the expression of connective tissue growth factor, fibronectin, and α-SMA[ 65 ]. However, in a coculture model of ASCs and normal human dermal fibroblasts, ASCs increased the formation of collagen types I, III, and VI in the ECM[ 66 ]. It appears that ASCs could target abnormal fibroblasts and reduce pathological deposition of ECM.…”
Section: Mechanism Of Asc Therapymentioning
confidence: 99%
“…In another study, ASC-CM reduced the synthesis of collagen and the expression of connective tissue growth factor, fibronectin, and α-SMA[ 65 ]. However, in a coculture model of ASCs and normal human dermal fibroblasts, ASCs increased the formation of collagen types I, III, and VI in the ECM[ 66 ]. It appears that ASCs could target abnormal fibroblasts and reduce pathological deposition of ECM.…”
Section: Mechanism Of Asc Therapymentioning
confidence: 99%
“…Auxenfans et al [ 69 ] also demonstrated that a 3D-reconstructed skin model co-cultured with ASCs increased thickness of the dermis, specifically the papillary dermis. In direct juxtacrine co-culture and in indirect paracrine co-culture, ASCs improved collagen maturation and metalloproteinase secretion compared to monoculture [ 70 ].…”
Section: White Adipose Tissuementioning
confidence: 99%
“…[ 18 ] Next, we investigated the bioactivity of PIC‐E2 on adipose‐derived stem cells (ASCs), because they are often used for various tissue engineering applications including POP; [ 19 ] ASCs possess various regenerative capabilities including stimulation of ECM production and their angiogenic and immunomodulatory potential. [ 20 ] We hypothesize that the combination of PIC‐E2 and ASCs may have a synergistic therapeutic effect on the regeneration of the pelvic floor in vivo and, hence, may improve surgical outcomes of POP.…”
Section: Introductionmentioning
confidence: 99%